SOSIALISASI PANGAN SEHAT BAGI REMAJA DI SMP YOS SUDARSO PADANG - Reny Salim; Tuty Taslim; Fita Selonni; Verawaty Verawaty; Irene Puspa Dewi; Tumpal Manurung (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT, POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN PALEMBANG, 2022)
Teenagers need socialization about the types of food and drinks they consume. Food and beverages influence the intake of nutrients required by the body. This devotion aims to determine the influence of socialization on adolescents' perceptions of balanced nutrition and see whether or not there is a relationship between knowledge and attitudes, knowledge by action, and perspective with activities in choosing a menu of food and drinks. The socialization method used is creative lectures. Participants consisted of teenagers aged 10-11 years. The instruments used are test sheets and questionnaires. The results obtained from the pretest and posttest showed that socialization influenced changes in teenagers' perceptions of the fulfillment of balanced nutrition. Still, there was no relationship between knowledge and attitudes or knowledge with actions or attitudes with adolescent actions in the selection of food and drink menus. The result means that adolescents need continuous guidance from their families, schools, and the surrounding environment about healthy food and drink menus to fulfill balanced nutrition.